The Impact of Information Culture on Patient Safety Outcomes - Jylhä, Virpi; Mikkonen, Santtu; Saranto, Kaija; Bates, David W. (Methods of Information in Medicine, 2017)
Background: An organization’s information culture and information management practices create conditions for processing patient information in hospitals. Information management incidents are failures that could lead to adverse events for the patient if they are not detected.Objectives: To test a theoretical model that links information culture in acute care hospitals to information management incidents and patient safety outcomes.Methods: Reason’s model for the stages of development of organizational accidents was applied. Study data were collected from a cross-sectional survey of 909 RNs who work in medical or surgical units at 32 acute care hospitals in Finland. Structural equation modeling was used to assess how well the hypothesized model fit the study data.Results: Fit indices indicated a good fit for the model. In total, 18 of the 32 paths tested were statistically significant. Documentation errors had the strongest total effect on patient safety outcomes. Organizational guidance positively affected information availability and utilization of electronic patient records, whereas the latter had the strongest total effect on the reduction of information delays.Conclusions: Patient safety outcomes are associated with information management incidents and information culture. Further, the dimensions of the information culture create work conditions that generate errors in hospitals.
Keywords: Information management; patient safety; adverse events; medication administration error; patient complaint; survey; health information technology